2022
DOI: 10.1101/2022.03.30.486378
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sabatier principle for rationalizing enzymatic hydrolysis of a synthetic polyester

Abstract: Interfacial enzyme reactions are common in nature and in industrial settings, including the enzymatic deconstruction of poly(ethylene terephthalate) (PET) waste. Kinetic descriptions of PET hydrolases are necessary for both comparative analyses, discussions of structure-function relations and rational optimization of technical processes. We investigated whether the Sabatier principle could be used for this purpose. Specifically, we compared the kinetics of two well-known PET hydrolases, leaf-branch compost cut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 50 publications
1
5
1
Order By: Relevance
“…In such interfacial catalysis, the reaction rate is hyperbolic with respect to enzyme concentration, due to the saturation of accessible scissile bonds on the substrate. [15,17] In contrast to this, here we have shown that for IsPETase and numerous mesophilic homologues, the extent of reaction is not hyperbolic in profile; instead, it reaches a maximum then falls as the enzyme concentration rises. [2,15,20] In this study, we analyzed concentration-dependent inhibition in multiple natural IsPETase homologues and engineered variants of IsPETase itself, and we demonstrated that the extent of inhibition on PET is related to the dynamic properties of the enzyme, including regions around the active site; less thermostable enzymes are often more susceptible to inhibition at high enzyme concentration.…”
Section: Discussioncontrasting
confidence: 86%
“…In such interfacial catalysis, the reaction rate is hyperbolic with respect to enzyme concentration, due to the saturation of accessible scissile bonds on the substrate. [15,17] In contrast to this, here we have shown that for IsPETase and numerous mesophilic homologues, the extent of reaction is not hyperbolic in profile; instead, it reaches a maximum then falls as the enzyme concentration rises. [2,15,20] In this study, we analyzed concentration-dependent inhibition in multiple natural IsPETase homologues and engineered variants of IsPETase itself, and we demonstrated that the extent of inhibition on PET is related to the dynamic properties of the enzyme, including regions around the active site; less thermostable enzymes are often more susceptible to inhibition at high enzyme concentration.…”
Section: Discussioncontrasting
confidence: 86%
“…The results of the TIRF experiments suggest that PET hydrolases spend enough time on a PET surface to hydrolyse a number of bonds, given that the enzyme turnover number (k cat ) of LCC ICCG is approximately 0.3 s À 1 under relevant conditions. [14] However, the non-specific binding model suggested based on the TIRF data in this study would support the conclusion that the majority of enzymes bound to the surface of PET do not exhibit processive behavior. Furthermore, the results from the FRAP experiments indicate negligible lateral diffusion over the PET surface, as discussed below.…”
Section: Lateral Diffusion Assays Using Frap Microscopysupporting
confidence: 56%
“…This has also been suggested previously when comparing LCC ICCG to other PET hydrolases, in accordance with the Sabatier principle, which states that the optimum activity of a protein often occurs when an enzyme has an intermediate affinity, being neither adsorption or desorption limited. [14] It has also been recently shown that the two enzymes produce markedly different degradation profiles on a PET surface, [27] with PHL7 producing a crater-like effect on the surface, whereas LCC ICCG produces a smoother surface upon degradation. This observation could also be due to the longer residence time of PHL7 compared to LCC ICCG , as the longer an enzyme spends in one position, the more likely it is to bore into the surface.…”
Section: Pet Hydrolase Association and Dissociation Rate Constants Me...mentioning
confidence: 99%
See 1 more Smart Citation
“…We note that DMSO has previously been shown to either modestly suppress or enhance the enzymatic efficiency of PET-hydrolases for bulk reactions on PET. [23,45,46] Duplicates and substrate blanks (for quantification of autohydrolysis) were included, and all reactions were quenched and analyzed by RP-HPLC as described above.…”
Section: Determination Of Kinetic Constantsmentioning
confidence: 99%